Is Nurses' Job Satisfaction Related to Occupational Health and Safety Management? - Saeed Khaleghi; Ali Sadeghi Moghaddam; Yaser Moradi; Hossein Jafarizadeh; Mostafa Ghalavand; Mohsen Poursadeghiyan; Seyed Habibollah Kavari (Tehran University of Medical Sciences, 2021)
No Abstrct